Variabilidade espacial dos atributos químicos do solo, índices de vegetação e sua relação com atributos químicos do mosto da uva - Agnol, Odair Dal (2016)
Viticulture in Rio Grande do Sul state occupies a prominent position in the national scenario, the sector accounts for about 60.2 % of the total cultivated area in the country. Vine cultivation has very important economic and social, as well as a production chain organized in the different producing regions. The aim of this study was to quantify the spatial variability of the chemical attributes of the grape must, chemical soil properties, vegetation indices and verify possible correlations between variables. The study area consisted of a vineyard with 3.09 ha of farming Bordô (Ives) grafted onto the rootstock Paulsen, located in the trough line, in the municipality of Sarandi - RS. In a mesh composed of 34 sampling points soil samples were collected in a depth range from 0 to 20 cm. Analyses were performed in the laboratory of soil analysis at the Federal University of Santa Maria (UFSM), the chemical attributes analyzed were: clay; pH in H2O; SMP, P; K; organic matter; al; Here; mg; H + Al; CTC effective; CTC pH7; Base saturation; relationship between Ca and Mg; Zn; Cu; S and B. The analysis of grape must was held in the chemistry laboratory of the Federal Institute Farroupilha campus Panambi studied enological parameters were: total soluble solids; titratable acidity and pH in organic acid. The determination of vegetation indices was carried out in situ in the 34 sampling points with use of spectroradiometer. The data were submitted to descriptive statistical analysis and Geostatistics, using the computer program for such Geoestatistics for the Environmental Sciences (GS +), Pearson correlation coefficients were determined with the aid of Excel. Analysis of the spatial variability of the data was based on the experimental semivariogram and from adjusted models interpolation was performed by ordinary Kriging, Stochastic Simulation and map algebra. Only the figures for the amount of total soluble solids showed low values other chemical attributes must show proper values. The results of soil analysis identified low concentrations of B and organic matter and high for the other attributes. From the overall analysis of the statistical dependence between variables, there was no significant correlations between the chemical properties of grape must and the other variables, unlike the segmented analysis according to the different harvest dates. The spatial dependence index of most chemical properties of soil studied was considered strong, only the attributes, Cu, Effective CTC CTC in pH7 and Clay did not present spatial dependence structure. Vegetation indices, except TVI2 showed strong spatial dependency ratio. Chemical attributes of the grape must, the concentration of soluble solids did not present spatial dependence structure, while others showed strong spatial dependence. In the result of map algebra the middle class of titratable acidity in organic acid added to middle class NDVI was representing the highest.